A PHARMACOGNOSTIC AND PHYTOCHEMICAL STUDY ON THE MARKET SAMPLES OF NAGAKESARA - S, *Nikath; Bulusu, Sitaram; P, Suneela (International Journal of Ayurveda and Pharma Research, 2018)
This work was conducted to evaluate the pharmacognostic and phytochemical study of varieties of Nagakesara. When it is further studied, it is observed that Nagakesara available in the markets of different areas is from different source plants. There are nearly 5 drugs sold in the market with the same name, the common floral parts available in the markets are commonly from Nagakesara (Mesua ferrea Linn.), Surapunnaga (Ochrocarpus longifolius Benth and Hook f.), Tamalpatra (Cinnamomum tamala Nees and Ebern.), Punnaga (Calophyllum inophyllum Linn.), Dillenia pentagyna Roxb. Hence a comparative study of these two samples 1) Nagakesara (Mesua ferrea), and 2) Tamalpatra (Cinnamomum tamala) has been carried out. The phytochemical study shows the presence of tannins, steroids and carbohydrates in almost all varieties of Nagakesara. Flower buds of Nagakesara plant of different species available in the market was taken up for the study. CONCLUSION: A detailed Pharamcognostic and Phytochemical review was done through which it was concluded that Mesua ferrea Linn. belonging to family Guttiferae may be the exact source of Nagakesara. The flower buds of Cinnamomum tamala Nees and Ebern. which is known as black variety in the markets according to our study,.